1994
DOI: 10.1083/jcb.127.1.203
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of bFGF gene expression and subcellular distribution of bFGF protein in adrenal medullary cells.

Abstract: Abstract. Basic fibroblast growth factor (bFGF), a potent mitogenic/neurotrophic factor, controls the development and plasticity of many types of neural cells. In adrenal chromaflin cells, the appearance of bFGF protein coincided with the establishment of functional innervation, suggesting induction by trans-synaptic signals. In cultured bovine adrenal medullary cells Western blot analysis revealed 18-, 23-, and 24-kD bFGF isoforms in the cytosolic and nuclear fractions. Stimulation of acetylcholine nicotinic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
147
1

Year Published

1997
1997
1999
1999

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(163 citation statements)
references
References 91 publications
15
147
1
Order By: Relevance
“…Three protein isoforms were identified in Western blot analysis, in accordance with previous reports. 32 All three isoform levels were increased to a similar extent after TH FGF-2 injection. A kinetics analysis was run by examining FGF-2 levels 4, 7, 15 and 30 days after vector injection: maximal increases have been observed at 4 days, while a lower, nonsignificant increase was still present at 7 days, and levels returned to baseline by 15 days (Figure 5b).…”
Section: Figure 2 Western Blot Analysis Of Fgf-2 Expression 24 H Aftementioning
confidence: 84%
“…Three protein isoforms were identified in Western blot analysis, in accordance with previous reports. 32 All three isoform levels were increased to a similar extent after TH FGF-2 injection. A kinetics analysis was run by examining FGF-2 levels 4, 7, 15 and 30 days after vector injection: maximal increases have been observed at 4 days, while a lower, nonsignificant increase was still present at 7 days, and levels returned to baseline by 15 days (Figure 5b).…”
Section: Figure 2 Western Blot Analysis Of Fgf-2 Expression 24 H Aftementioning
confidence: 84%
“…Heparin-sepharosebound proteins were eluted directly into SDS sample bu er and resolved by SDS ± PAGE gel electrophoresis on a 12% polyacrylamide gel. Proteins were transferred onto nitrocellulose membranes and Western analysis performed using an anti-FGF-2 monoclonal antibody (UBI, Lake Placid, NY) followed by rabbit anti-mouse IgG and 125 I-labeled protein A (Florkiewicz and Sommer, 1989;Stachowiak et al, 1994). In some experiments 10 ml of conditioned media were processed through heparin sepharose and analysed in a similar way to the cell extracts to determine whether FGF-2 was present in the media.…”
Section: U251mg Sf767 Sf763mentioning
confidence: 99%
“…Nuclear presence of FGF-2 was detected in rat brain astrocytes both in vivo (Woodward et al, 1992) and in vitro (Vijayan et al, 1993) and in cultured human astrocytes and glioma cells (Mo ett et al, 1996;Stachowiak et al, 1996a). With the observation that FGF-2 remains cell associated and may not be secreted by a classical mechanism, a regulated targeting of endogenous FGF-2 to the nucleus (Puchacz et al, 1993;Stachowiak et al, 1994Stachowiak et al, , 1996bMo ett et al, 1994Mo ett et al, , 1996 suggests that this growth factor may serve as an intracrine signaling molecule.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deletion analysis indicated two negative regulatory elements, one of which is in the upstream promoter region. It was reported that the bFGF promoter was induced by PMA and cAMP through cis regulatory elements (Stachowiak et al, 1994). An AP-1 element in the bFGF promoter has been shown to be functional in the transcriptional regulation of bFGF gene expression Erdos et al, 1995).…”
Section: Introductionmentioning
confidence: 99%